The Indirect Costs of Financial Distress in Indonesia - Wijantini, Wijantini (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
This paper presents quantitative estimates of the indirect cost of financial distress and its determinants. In order to measure the cost, this study estimates the annualized changes in industry-adjusted operation profit and sales from a year before the onset of distress to the resolution year. Using those approaches, the median of indirect financial distress cost is estimated between three and 11 percent annually. To the extent that the direct cost of financial distress reduces reported operating income, the estimated costs are overstated. The simple regressions analysis suggest that the indirect cost of financial distress significantly increases with size, leverage, number of creditors, and poor industry performance, but is not related to degree of bank loan reliance. The findings provide a weak support for the financial distress theory which suggests that conflicts of interest render the costs of financial distress.